ESTIMATE FREEWAY EXIT SIGN LOCATIONS - PROF. Y. GEORGE, DR. JEOB L.F; MICKAL KHIR (International Journal of Multidisciplinary Research and Studies, 2020)
Considering that a driver decides to exit a highway upon seeing the guide sign upstream of an exit, subsequently, the driving force in an enclosed lane or the center lanes must move onto the skin lane before exiting. The priority is whether or not the motive force can accomplish this task safely and smoothly. It’s apparent that an upstream exit sign cannot be placed too near an exit or too far beyond several exits upstream. The MUTCD recommends that the sign should be placed 1 mile and a couple of miles upstream of an exit without explaining the explanations for choosing the 1-mile distance. By integrating driver decisions, vehicle acceleration characteristics, tire-road traction into one analytic framework, the situation upstream of an exit where an exit sign should be installed is set for a driver to induce off at the proper exit successfully. Practitioners can easily apply these user-friendly formulae and equations derived from the framework to compute the specified distance ‘D’ between a highway exit and an upstream exit sign for guiding drivers to exit the highway safely. Additionally, parameters for these formulae are adjusted to resemble various exiting scenarios.